The Relevance of Current Accounting Standards in Measuring Intellectual Capital and Their Impact on Banking Performance - Laiza Shendy Rindhyanti; Yusnaini Yusnaini (GLOBAL SCIENTS PUBLISHER, 2026)
This research intends to systematically review and synthesize the current landscape of accounting research regarding the implementation of updated accounting standards (PSAK 71/IFRS 9) and the role of Intellectual Capital (IC) in the banking sector. It explores how the shift from the incurred loss model to the Expected Credit Loss (ECL) model engages with intangible assets to affect financial outcomes and the quality of reporting. This paper examines 34 high-quality peer-reviewed articles published from 2020 to 2026 through a Systematic Literature Review (SLR) method. The dataset encompasses a variety of geographical settings, primarily emphasizing Indonesia and Europe. The analysis categorizes the literature based on theoretical frameworks, research variables, and empirical outcomes. The results indicate the implementation of PSAK 71 greatly improves the forecasting capability of financial statements but introduces substantial managerial discretion. From a Signaling Theory perspective, banks leverage IC disclosures to mitigate information asymmetry caused by the complexity of ECL. Resource-Based View (RBV) analysis reveals that Human and Structural Capital are critical for absorbing the volatility of loan loss provisions. However, Agency Theory highlights risks of opportunistic earnings management through subjective staging and forward-looking parameters. Empirical results show a predominantly positive correlation between IC efficiency and bank resilience, although the impact on net profit is often dampened by increased impairment charges. Regulators should standardize macroeconomic parameters to limit excessive managerial discretion. For bank management, investing in Artificial Intelligence (AI) and digital infrastructure (Structural Capital) is essential to ensure the technical integrity of ECL modeling and to maintain stakeholder trust. This study provides a comprehensive nexus between modern accounting standards and Intellectual Capital, offering a dual perspective on how regulatory compliance and intangible assets jointly determine the sustainability of the banking industry in a volatile economic era.